2003
DOI: 10.1016/s0029-7844(03)00618-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hormonal contraceptives on the immune cells and thickness of human vaginal epithelium

Abstract: Hormonal contraceptives induce hyperplasia of the vaginal epithelium. The significant changes in the intraepithelial leukocyte population in depot-medroxyprogesterone acetate and levonorgestrel implant users most probably reflect altered local immune capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 31 publications
6
46
1
1
Order By: Relevance
“…11,27 Changes in vaginal mucosal immune cell populations have been demonstrated in women using DMPA, likely reflecting altered local immune function. 28 This could in turn influence the risk for BV. Injectable progesterone contraception may also modify the risk of BV by reducing menstrual frequency and volume.…”
Section: Discussionmentioning
confidence: 99%
“…11,27 Changes in vaginal mucosal immune cell populations have been demonstrated in women using DMPA, likely reflecting altered local immune function. 28 This could in turn influence the risk for BV. Injectable progesterone contraception may also modify the risk of BV by reducing menstrual frequency and volume.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that hormonal contraceptives may affect human immunodeficiency virus (HIV) susceptibility within the vaginal vault by modulating the genital immune system, regulating genital epithelial cells, inducing cervical ectopy, and affecting the local microflora [2][3][4][5][6]. Data regarding vaginal epithelial thickness differences between hormonal contraceptive users and nonusers are however indecisive, and the clinical relevance of some of these limited changes is unclear [7][8][9][10][11][12]. Thus, the global impact of the biological effects of hormonal contraceptives needs to be explored in detail to understand how they may affect susceptibility to HIV acquisition and transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Immune cells, including HIV target cells, are also present in the multistratified epithelium of the ectocervix and may be differentially distributed under the influence of exogenous sex hormones [3,9,[31][32][33]. Thus, superficially located T cells and Langerhans cells expressing CD4, CCR5, and Langerin can potentially bind HIV particles in the presence of small breaches or in ectocervical and vaginal tissue affected by inflammation [34].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this dose does not recapitulate the biological effects seen in women. For example, in women, 150 mg DMPA results in moderate thinning of the vaginal epithelium with one study even reporting thickness due to hyperplasia [10][11][12]. In contrast, 30 mg of DMPA in macaques reduces vaginal epithelial thickness by approximately 80% [7].…”
Section: Introductionmentioning
confidence: 99%